(untitled) (Research, Society and Development, 2021)
The size and spatial structures of populations are a synthesis of demographic attributes and indicators of competitive ability, colonization, and survival. In this study, the objective was to analyze the height and spatial pattern of an understory and canopy/emergent tree populations group in two protected fragments of seasonal semideciduous forest, one with a history of selective logging and another without selective logging evidences. Six species with high importance values (IV) from different guilds were selected and height and spatial pattern analysis was realized in both areas. Then, comparison of results was realized in an area with history of selective logging and another without selective logging evidences. Differences in height and spatial pattern were found between the two areas, including species not directly exploited. In Logged Forest the size structure for all species presented a higher coefficient of skewness, showing a greater proportion of young trees. Random distribution was observed for the majority of species in both areas. Some emergent/canopy species had a deficit of individuals in the largest size classes and the majority of understory species showed more individuals in Logged Forest. Selective Logging changed the pattern of populations. Selecting species based on IV together with spatial patterns data contribute to demonstrating the impacts of exploitation. The Logged Forest is surrounded by an agricultural matrix, limiting arrival and dispersion of propagules of shade-tolerant species. Efforts to connect surroundings fragments to Logged Forest will be necessary.